Some critical consideration in relations to the historiographical approximations reserring to the political-electoral situation of 1939 in Peru - Molinari Morales, Tirso (2019)
A critique is hereby provided which attempts cognitively to be as precise as possible, to certain and important historiographic explanations referring to the serious political-electoral situation of 1939 in Peru given the series of documentary limitations and/ or interpretative deficiencies that those explanations pose, and also given the disastrous fraudulent consequences derived from the extreme dictatorial context.